Communicating the Turkish Military Strength and Organisation after the Crusader Defeat at Nicopolis: Comparing Philippe de Mézières Une Epistre lamentable, Honorat Bovet’s L’Apparicion Maistre Jehan de Meun and Bertrandon de la Broquière’s Le Voyage d’Outremer - Kocabıyıkoğlu Çecen, Zeynep (Religions, 2023)
The outcome of the Nicopolis crusade (1396)—a crushing victory for the Ottoman Turks over a crusader army led by Franco-Burgundian knights—had particularly deep resonances in the Kingdom of France. This was reflected in several contemporary works that lamented and/or criticised the crusaders’ defeat. Among these, Philippe de Mézières’s Une Epistre lamentable (1397) and Honorat Bovet’s L’Apparicion Maistre Jehan de Meun (1398) are of special note because they contain not only remarkable reflections on the campaign but also interesting observations on the successful Ottomans. Their praise of the Turks, especially regarding their military organisation and discipline, served both to criticise the crusaders’ own lack of discipline but also to present an example for them to follow in order to avenge the defeat. As Nicopolis marked the beginning of a Burgundian claim to champion the crusading movement, these works were primarily addressed to the Duke of Burgundy, among other European princes and nobility. In the mid-fifteenth century, Duke Philip the Good would carry this claim to its zenith by several undertakings that included sending envoys to the East to gather information about the enemy. One of these envoys, Bertrandon de la Broquière, visited the Ottoman lands in 1432–1433 and some twenty years later wrote his Le Voyage d’Outremer to communicate the observations and intelligence gathered during his journey. The fact that this work, written almost six decades after Nicopolis, contains multiple allusions to the defeat, in addition to similar portrayals and comments on the Turks within the two earlier works, can be taken to suggest a continuity in Western military portrayals of the Turks from Nicopolis onwards.